Newcomer leader–member exchange: the contribution of anticipated organizational support. Issue 4 (29th September 2016) - Zheng, Dianhan; Wu, Hao; Eisenberger, Robert; Shore, Lynn M.; Tetrick, Lois E.; Buffardi, Louis C.
Abstract : We surveyed 198 graduating college seniors at four points before and after they began a new job to examine the relationship between anticipated organizational support (AOS) and leader–member exchange (LMX) as mediated by information seeking. We found that AOS, assessed before the first day of work, was associated with subsequent LMX 3 months after work began. Furthermore, information seeking mediated the relationship between AOS and LMX. Moreover, LMX was associated with reduced psychological strain, lessened turnover intentions, and increased extra‐role behaviours 6 months following the start of work. These findings indicate that anticipation of future support before the onset of employment influences newcomers' LMX and its consequences. Practitioner points: Human resources practitioners and managers can prepare a better transition for newcomers by cultivating a supportive and caring view of the organization before the newcomers start their job. To enhance such anticipated organization support, the organization's positive valuation of the newcomers and concern with their welfare can be emphasized during job interviews with prospective employees and training sessions. Educating supervisors to be responsive to newcomers' requests for information may contribute to their adjustment and help them meet organizational goals and objectives.